Vorurteile und Stereotype im Vereinssport: Eine Analyse im Kontext von Sozialisation und Antidiskriminierung - Delto, Hannes (transcript, 2021)
An innovative look at the significance and function of prejudice in sport-related socialization based on high empirical explanatory power.